Dampak Konversi Lahan Perkebunan Kelapa Lokal menjadi Perkebunan Kelapa Sawit dalam Perspektif Ekonomi Syariah di Desa Kuala Keritang, Indragiri Hilir, Riau - Saihuna Saihuna; Ahsan Putra Hafiz; Muhamad Subhan (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This aims to reveal the Impact of Converting Local Coconut Plantation Land into Oil Palm Plantations in an Islamic Economic Perspective in Kuala Keritang Village, Kec. Keritang, Kab. Indragiri Hilir, Riau. This thesis uses a qualitative approach by collecting data through observation, interviews, and documentation. The background causes the rubber farmers to switch functions to become oil palm farmers in Kuala Kritang Village is that work as a local coconut farmer is carried out every day and requires difficult maintenance while the price is cheap so that the farmer's income is not enough to meet economic needs. While oil palm work is only once every two weeks, it is more expensive than rubber and is sufficient to meet daily needs. The impact on the welfare of the families of local coconut farmers after the conversion to oil palm farmers in Kuala Kritang Village has a positive impact on farmers, their income increases, work is lighter, there is an increase in assets owned, and families feel more prosperous. If viewed from Maqasid Syariah, the impact of converting local coconut plantation land to oil palm for the economy of the people in Kuala Keritang Village is in accordance with Islamic Sharia.